The level of understanding of plant physiology in caring for ornamental plants - Emayulia Sastria; Dharma Ferry; Winda Ayu Fietri (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to determine the level of understanding of plant physiology in caring for ornamental plants in the people of Sungai Penuh City. This understanding is related to the understanding of Plant Physiology. If the community already has an understanding of plant physiology, then the community can take advantage of ornamental plants such as greening their homes, increasing income, and being used as medicinal plants. The type of research used is quantitative research with a descriptive approach. The population and sample in this study were the people of Sungai Penuh City, amounting to 76 people. The instrument used is a test in the form of questions about people's understanding of plant physiology. Data analysis using SPSS and using the percentage formula. The results showed that the understanding of community plant physiology in caring for ornamental plants can be seen that 27 respondents scored